IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH DALAM PENGENTASAN KEMISKINAN (STUDI DI DISTRIK KUARI KABUPATEN TOLIKARA PROVINSI PAPUA - Liwiya, Yunier; Pangkey, Masje Silija; Tampi, Gustaf Budi (Sam Ratulangi University, 2018)
ABSTRACT: Research Objectives To know the implementation of local government policies in povertyalleviation, in the District of Tolikara District of Papua ProvinceMethods in this study using qualitative research methods To find ganbaran about the survival of the poorin Kuari District. the qualitative analysis technique used is the analyst of intractive model. Technique ofcollecting data in this research is done by observation (observation), depth interview and documentationstudyThe results show that the implementation of local government can not run well if the policy standards andtargets are vague and unmeasurable, in the implementation of the district government tolikara kuari district.people who are not yet aware of the importance of education and health, the problem of poverty seen fromthe perspective of food is a problem of food insecurity due to low purchasing power, uneven food availability,high dependence on tbsp and limited diversification of food.Keywords: Policy Implementation, Local Government and Poverty Alleviation